The prognostic value of national early warning scores (NEWS) during transfer of care from community settings to hospital: a retrospective service evaluation. Issue 2 (June 2020) - Kim, Matthew Inada-; Ainsworth-Smith, Mark; Lasserson, Daniel; Knight, Thomas; Pike, Neil; Richardson, Mathew; Sullivan, Michelle; Hayward, Gail
No abstract available